Helex device closure of multiple atrial septal defects. Issue 2 (21st April 2014) - Mehta, Smita; Hill, James A.; Qureshi, Athar M.; Latson, Larry A.; Prieto, Lourdes R.
<x xml:space="preserve">Abstract</x> Objectives : To describe the effectiveness of the Helex Septal Occluder (HSO) to close multiple atrial septal defects (mASDs). Background : Limited information is available describing closure of mASDs with the HSO. Methods : A total of 28 patients who underwent closure of mASDs with the HSO were identified by retrospective review of our catheterization database between 2001 and 2012. Procedural details and follow up information were collected. Results : Median age was 19.2 years, median weight 48 kg, with 10 (36%) patients weighing <25 kg. Indication for closure was RV enlargement (RVE) in all patients and additionally neurologic events occurred in 3/28 (11%). Median stop‐flow diameter for the largest ASD was 14 (4–23) mm. One HSO was implanted in 21/28 (75%), 2 in 6/28 (21%), and 3 in 1/28 (4%). One embolization and one transient arrhythmia occurred with no sequelae. Immediate residual shunt was absent in 5/28 (18%), trivial in 15/28 (54%), small in 6/28 (21%), and moderate in 2/28 (7%). Of the 25 patients with ≥6 months follow‐up (median 53 months), residual shunt was absent in 13/25 (52%), trivial in 5/25 (20%), and small in 7/25 (28%). RVE resolved in all but one patient with no other associated lesions and ≥6 months of follow‐up. No patient with prior neurological event had recurrence at last follow‐up. Conclusions : We conclude that closure of mASDs with ≥1 HSO is effective with a low complication rate. The ability of HSO devices to overlap or sandwich each other may facilitate safe implantation of multiple devices in smaller patients. © 2013 Wiley Periodicals, Inc.